Does a Customer on the Board of Directors Affect Business-to-Business Firm Performance?. (January 2019) - Bommaraju, Raghu; Ahearne, Michael; Krause, Ryan; Tirunillai, Seshadri
The authors hypothesize that customer presence in the boardroom of business-to-business (B2B) firms brings customer orientation and customer knowledge to the board of directors and thereby enhances B2B firm performance. Using an objective measure of customer presence in the boardroom and a sample of 329 B2B firms over a nine-year period, the authors find support for this hypothesis. Moreover, relying on the resource-based view, they hypothesize that the performance benefit of customers in the boardroom is contingent on the value, rarity, inimitability, and organizational fit of customer resources. Specifically, they find that a customer on the board is more effective when demand uncertainty is high but is less effective when the firm is highly diversified. Moreover, a board member who is an independent director of the customer firm is less effective than a board member who is an executive at the customer firm. The authors also find that research and development intensity partially mediates the relationship between customer presence on the board and firm performance.